Presenting the proposed model of media soft power components to improve the combat capability of the Army of the Islamic Republic of Iran - FARHANG, SAJJAD; SAMADI, MEHRAN; HASHI, ALI TAHERI; DANA, HAMIDREZA HOSSEINI (The journal of contemporary issues in business and government, 2021)
Due to its sensitive strategic and geopolitical position, the Islamic Republic of Iran is obliged to strengthen the dimensions of its soft power while paying attention to strengthening various aspects of hard power. Iran can use its soft power and achieve the strengthening of its national power when it presents its strategy and strategy as well as its desired values in such a way that it utilizes the components of its power production components from both national and transnational dimensions. Brought. The purpose of this article is to design a model of soft media power in order to improve the combat capability of the Army of the Islamic Republic of Iran using the ground-based approach. In this study, in order to identify the indicators of soft power in promoting the combat capability of the army of the Islamic Republic of Iran, experts’ opinions were used. Four basic indicators for soft power were determined, which are in order of priority: Army, changing the rules of the armed forces, parallel armed forces in the country, armed forces of foreign countries) in the media dimension (national media, new media, foreign media, hardware and software facilities) in the cultural dimension (orbital province, God-centered, Basij thinking And then manpower (creativity, participation in organizational decision-making, elites and professors inside the organization, elites and professors outside the organization, training, Q&A sessions, improving organizational communication, improving staff livelihoods).